Propriedades químicas da arsenopirita, adsorção de agentes lixiviantes e seu mecanismo de oxidação a partir de cálculos DFT - Juliana Cecília de Mendonça Silva (2016)
Sulfide minerals, among them arsenopyrite, are commonly present in mining tailings and are responsible for acid rock drainage (ARD). In this phenomenon, the mineral undergoes oxidation in contact with oxygen and water and produces a liquid containing acid and heavy metals capable of contaminating the environment. Mitigation of the ARD problemand the development of countermeasures are facilitated by understanding its mechanism. Therefore the knowledge of the sulfides oxidation process is very important, especially of arsenopyrite, which, in addition to ARD, also releases the toxic element arsenic by itsoxidation. This process is not yet completely understood, since the reactions involved are very complex, which leads to a lack of consensus in the literature. In this context, first principle calculations can contribute to the understanding and interpretation of the experimental data in the elucidation of the reaction mechanism at a molecular level.In this thesis, the structural, electronic and mechanical properties of arsenopyrite, its chemical bonds and its surfaces cleavage, as well as the adsorption of leaching agents and its oxidation mechanism have been investigated by DFT calculations. Evidences showingthat there is no FeFe bond in arsenopyrite and that the AsS bond has strong covalent character have been provided. It has been also shown that this strong AsS bond is unlikely to be broken during the surface formation. The preferential cleavages are predicted to occurin the planes (001), (010) and (100). The (001) surface is the one that presents the lowest surface energy, and has magnetic properties. The adsorption of water on this surface is most favorable in molecular form on the most exposed Fe sites. Hydrochloric acid favors dissociative adsorption and sulfuric acid prefers the molecular monodentate adsorption form, while bisulfate adsorbs in bidentate binuclear coordination. The adsorption of sulfate is predicted to be not favored. The adsorption of oxygen on the Fe site is very favorable, especially dissociatively, when a FeOAs bridge is formed. In this process, both Fe and As atoms are oxidized. The co-adsorption of oxygen and water on the surface is also stable. An oxidation mechanism for arsenopyrite has been proposed, in which the oxygen is adsorbed to the surface and receives H atoms from water molecules, which again reduces the Fe. Inthe proposed mechanism, arsenic is the element that preferentially oxidizes, which explains the available experimental data. Calculations for pyrite have also been performed and compared with arsenopyrite, aiming to provide significant insights about both systems.